ORGANIC REMOVAL IN DOMESTIC WASTEWATER USING ANAEROBIC TREATMENT SYSTEM-MBBR WITH FLOW RECIRCULATION RATIO AND INTERMITTENT AERATION - Michael Subroto; Wisnu Prayogo; Prayatni Soewondo; Ahmad Soleh Setiyawan (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2022)
Aim: The modified Small-scale Domestic Sewage Treatment Plant (SDSTP) reactor with anaerobic fixed bed- aerobic Moving Bed Biofilm Reactor (MBBR) is implemented to find the optimum condition for organic degradation related to recirculation and intermittent aeration practices with the purpose to comply with the governmental regulation standard.  Methodology and Results: This research have been done with the artificial wastewater with characteristic similar to the sewage treatment plant (STP) of Telkom company with ratio C:N:P of characterized domestic wastewater is 252.40:85.42:3.01 that consists of glucose, NH4Cl, potassium dihydrogen phosphate, potassium nitrate, and sodium nitrite (NaNO2). Reactor design related with attached biomass in media until 2478.56 mg MLVSS.L-1 with the growth kinetics rate (μ) of 0.4691 day—1. The artificial wastewater is applied the determine the optimum variation of flow recirculation and periodic aeration in specific Hydraulics Retention Time (HRT) and Organic Loading Rate (OLR). In this research, the optimum recirculation ratio for organic degradation is 26.40 L.h-1 and the optimum aeration frequency variation is  12 hours in intermittent frequency with the maximum efficiency of organic degradation of 76.10% with the degradation efficiency real domestic wastewater application from STP Telkom company is 83.09%. Conclusion, significance and impact study:  Stover-Kincannon model is the best model with highest accuracy rate to model the degradation performance of organic compounds by the anaerobic fixed bed- aerobic MBBR SDSTP with determination coefficient 0.8623 and also degradation coefficient 38.121 day-1 compared with other models studied in this research.